تحليل أداء سوق الأسهم لبورصة الجزائر خلال الفترة (2013-2019) - سعيدي, حنان (جامعة الوادي - University of Eloued, 2020)
يعتبر وجود بورصة متطورة قادرة على التخصيص الأمثل للموارد المالية أداة فعالة في انعاش الاقتصاد الوطني ونموه، لذا تهدف هذه الدراسة إلى تحليل مختلف مؤشرات الأداء في سوق الأسهم لبورصة الجزائر، من مؤشر رسملة البورصة، نشاط التداول وعدد الشركات المدرجة وهذا خلال الفترة (2013-2019) من أجل تحديد مدى تطور أداء هذه السوق لاسيما بورصة الجزائر ككل، ومدى تأثيرها على الاقتصاد الوطني. خلصت الدراسة إلى أن سوق الأسهم تعاني من ضعف في الأداء بسبب محدودية الشركات المدرجة فيها مع ضعف حجم المعاملات بها والذي انعكس بالسلب على أداء بورصة الجزائر بشكل عام، ما جعلها لا تؤدي دورها المنتظر في تعبئة الادخار القومي وتوجيهه نحو قنوات استثمارية التي تعمل على دعم الاقتصاد الوطني وزيادة معدلات نموه، لذا قمنا بتقديم بعض التوصيات التي تعتبر ضرورية لتفعيلها. The presence of a developed stock exchange capable to the optimal allocation of financial resources is an effective tool to reviving and growing the national economy, so this study aims to analyze the various performance indicators in the stock market for the Algiers Stock Exchange, represented by the market capitalization index, trading activity and the number of companies listed during the period 2013-2019 in order to determine the extent of development of this market including the Algiers Stock Exchange as all and its impact on the national economy. The study concluded that the stock market suffers from a weak performance due to the limited companies listed on it with weak transactions, which negatively affected the performance of the Algiers Stock Exchange in general, which made it not perform its expected role in mobilizing national savings and directing it towards investment channels that support The national economy and increasing its growth rates, so we made some recommendations that are necessary to activate it
Analysis of the stock market performance for the Algiers Stock Exchange during the period 2013-2019
مقال
Keywords: أداء البورصة، الرسملة البورصية، بورصة الجزائر، سوق الأسهم، نشاط التداول.